1988
DOI: 10.1007/bf00394774
|View full text |Cite
|
Sign up to set email alerts
|

Coarse control of sucrose-phosphate synthase in leaves: Alterations of the kinetic properties in response to the rate of photosynthesis and the accumulation of sucrose

Abstract: It has been investigated whether diurnal rhythms of sucrose-phosphate synthase (SPS) are involved in controlling the rate of photosynthetic sucrose synthesis. Extracts were prepared from spinach (Spinacia oleracea L.) and barley (Hordeum vulgare L.) leaves and assayed for enzyme activity. The activity of SPS increased in parallel with a rising rate of photosynthesis, and was increased by feeding mannose and decreased by supplying inorganic phosphate. In leaf material where sucrose had accumulated during the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
200
3
2

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 266 publications
(216 citation statements)
references
References 19 publications
11
200
3
2
Order By: Relevance
“…Spinach (Spinacia oleracea US Hybrid 424, Ferry Morse Seed Company, Modesto, CA) was grown hydroponically in a 9 h light/l5 h dark cycle [9]. The catalytic subunits of PPl and PP2A [18], and inhibitors-l and -2 [IS] were purified to homogeneity from rabbit skeletal muscle; okadaic acid was a gift from Dr Y. Tsukitani, Fujisawa Pharmaceutical Company, Japan, and microcystin-LR was provided by Professor G. Codd, Department of Biological Sciences, University of Dundee.…”
Section: Methodsmentioning
confidence: 99%
“…Spinach (Spinacia oleracea US Hybrid 424, Ferry Morse Seed Company, Modesto, CA) was grown hydroponically in a 9 h light/l5 h dark cycle [9]. The catalytic subunits of PPl and PP2A [18], and inhibitors-l and -2 [IS] were purified to homogeneity from rabbit skeletal muscle; okadaic acid was a gift from Dr Y. Tsukitani, Fujisawa Pharmaceutical Company, Japan, and microcystin-LR was provided by Professor G. Codd, Department of Biological Sciences, University of Dundee.…”
Section: Methodsmentioning
confidence: 99%
“…However, the greater activity of INV and SS found in B. auleticus than in B. pictus might explain the lower con- centration of sucrose found in the northern species. Stitt (1988) showed that in order to see a modification of SPS activity, measurements had to be made with limiting substrate conditions. However, under low temperature, growth is severely reduced.…”
Section: Enzyme Determinationsmentioning
confidence: 99%
“…Phosphorylation leads to a lowering of the substrate affinity of the enzyme, and makes it more susceptible to inhibition by Pj and more dependent on Glc6P Siegl, Mackintosh & Stitt 1990). Reversible phosphorylation is involved in the regulation of SPS in response to rising rates of photosynthesis (Stitt et al 1988), accumulation of sucrose (Stitt et al 1988), the assimilation of nitrate (Van Quy & Champigny 1992) and water stress (Quick et al 1989;Zrenner & Stitt 1991;, although all the details of the regulation circuits have not yet been elucidated (see Huber & Huber 1996).…”
Section: Introductionmentioning
confidence: 99%